2013
DOI: 10.13076/tjo-d-13-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Orthodontic Malocclusion and Evaluation Criteria in 7 Geographic Regions of Turkey

Abstract: The aim of this study was to identify the prevalence of malocclusion and orthodontic evaluation criteria in Turkey and determine differences among the 7 regions. Materials and Method: In our research, extra-and intraoral examination of 1023 randomly selected persons from rural and central parts of different regions (500 female subjects and 523 male subjects; mean age = 13.10 6 3.11) were performed. To analyze the data, descriptive statistical methods (mean value, prevalence ratio, standard deviation) were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The included studies had diverse age groups ranging from 0 to 38 years old with a total sample size of 13,271 participants. Most of the studies were conducted only on permanent dentition (Akbulut, 2020 ; Başçiftçi et al, 2002 ; Celikoglu et al, 2010 ; Gelgör et al, 2007 ; Nur et al, 2014 ; Sayin & Türkkahraman, 2004 ; Ugur, 1998 ; Uzuner et al, 2015 ). However, a few of the studies recruited their sample from universities and dental (nonorthodontic) clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies had diverse age groups ranging from 0 to 38 years old with a total sample size of 13,271 participants. Most of the studies were conducted only on permanent dentition (Akbulut, 2020 ; Başçiftçi et al, 2002 ; Celikoglu et al, 2010 ; Gelgör et al, 2007 ; Nur et al, 2014 ; Sayin & Türkkahraman, 2004 ; Ugur, 1998 ; Uzuner et al, 2015 ). However, a few of the studies recruited their sample from universities and dental (nonorthodontic) clinics.…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence of malocclusions in the 10 studies reported the dental relations were 56% for class I, 31% for class II, and 11% for class III malocclusion (Akbulut, 2020 ; Başçiftçi et al, 2002 ; Celikoglu et al, 2010 ; Gelgör et al, 2007 ; Kaygisiz et al, 2015 ; Nur et al, 2014 ; Sari et al, 2003 ; Sayin & Türkkahraman, 2004 ; Uzuner et al, 2015 ; Yilmaz et al, 2006 ). Furthermore, the remaining 2% were allocated to normal and other types of occlusions such as class IV malocclusion (Celikoglu et al, 2010 ; Gelgör et al, 2007 ; Nur et al, 2014 ; Uzuner et al, 2015 ). Additional information is mentioned in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Cleft lip and palate (CLP) is a common congenital malformation. [8,9] The treatment of patients with CLP teeth emerge after birth (neonatal teeth); the intraoral plate may not fit and modifications of the plate may be required. In some cases, the therapy has to stop and postpone until the teeth has extracted.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The incidence is approximately 0.6% and more frequently recorded in Black Sea, South Eastern Anatolia, and Aegean region of Turkey. [2] CLP has a complex genetic and environmental etiology associated with dental anomalies. [3,4] Infants with CLP have esthetic and functional problems.…”
Section: Introductionmentioning
confidence: 99%